Measurement matters: the relationship between methods of scoring the Alternate Uses Task and brain activation. (June 2019) - Vartanian, Oshin; Beatty, Erin L; Smith, Ingrid; Forbes, Sarah; Rice, Emma; Crocker, Jenna
Highlights: The Alternate Uses Task (AUT) can be scored in multiple ways. Each AUT scoring approach reveals different mental processes and operations. AUT studies gain from intelligence, personality, and executive functions measures. AUT scoring approaches influence whether brain activation predicts performance. Neuroimaging studies of AUT would ideally adopt multiple scoring approaches. Abstract : Performance on the Alternate Uses Task can be measured using many approaches. The traditional approach involves scoring participants' output based on indices such as fluency, originality, and flexibility. The subjective approach involves using experts to rate output directly on creativity (or related constructs). The definitional approach involves rating output on novelty and usefulness—the two criteria deemed necessary and jointly sufficient to categorize an idea as creative. Measurement approaches influence firstly assessment of divergent thinking performance, secondly the relationship between performance and other constructs such as intelligence and executive functions, and thirdly whether brain activation predicts performance. We recommend that neuroimaging studies adopt multiple scoring approaches to generate more comprehensive assessments of the neural bases of divergent thinking performance.